The potential for submerged macrophyte recovery from the seed bank of the shallow coastal Whakakī Lake, Aotearoa : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Ecology at Massey University, Manawatū, New Zealand - Mackay, Ariana (Massey University, 2022)
Shallow lakes provide a range of ecosystem services, including habitat for waterfowl, fish, aquatic plants, and invertebrates, and have significant recreational, aesthetic, and cultural value. Eutrophication is one of the leading causes of shallow lake ecosystem degradation globally. Excess input of nutrients, especially phosphorus and nitrogen, can cause a regime shift where the ecosystem switches from a macrophyte-dominated system to one driven by primary production from phytoplankton. The naturally occurring communities dominated by aquatic macrophytes as primary producers undergo a drastic change, flipping to an algae-dominated state that can result in the degradation or disappearance of natural plant and animal communities. Whakakī Lake is a shallow coastal lake in northern Hawke’s Bay. This lake is in a highly degraded, hypertrophic state that no longer supports a community of submerged macrophytes. Previous work on the macrophyte community of Whakakī Lake in 1992 and 2007 provides an idea of the original condition of the macrophyte communities and the gradual decline in abundance and diversity that preceded the current conditions. Sediment coring at four sites along a transect was conducted in Whakakī Lake to quantify and characterise the seed and oospore bank of submerged macrophytes. A diverse and abundant seed bank was identified with 12 species of macrophytes and charophytes found throughout the lake. The highest abundance of seeds and oospores was located on the northern edges of the lake shore, near the Tuhara Stream inlet. Germination trials using the seeds and oospores collected from the seed bank were run over three months under controlled conditions to assess the viability of the Whakakī Lake seed bank. Species geminated under three salinity treatments: zero, low and moderate salinity levels. Light availability was altered to assess the impact of reduced light (photosynthetically available radiation) on species germination. The lack of germination success of seeds under severely reduced light levels and complete darkness demonstrated how high turbidity and lack of light is hindering seed germination within Whakakī Lake. With improvements to water quality, specifically the reduction of external and internal nutrient loads and increased water clarity, it is possible a submerged macrophyte community could re-establish within Whakakī Lake based on seeds and oospores available within the seed bank.
Keywords: 310304 Freshwater ecology